Analysis of contaminant mass in place in transmissive and low-k zones - Roads, Eric, author; Sale, Tom, advisor; Sharvelle, Sybil, committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2020)
Contaminant hydrology has been challenged by the common perception of homogeneous subsurface media. Previous sampling methods neglect the importance of differentiating between transmissive and low-k zones. Cryogenic core collection is a high-resolution sampling technique that can highlight the occurrence of transmissive and low-k zones as well as the distribution of contaminants in transmissive and low-k zones. Cryogenic core collection uses a CSU patented process that preserves core samples downhole using liquid nitrogen. Frozen cores are shipped to CSU on dry ice and always kept at -80ᵒC. Cores are cut into subsamples and analyzed to determine geology, physical properties, contaminant concentrations, and microbial ecology. The data is processed into Excel™ and then stored in gINT™, a relational database. Herein, consideration is given to 390 feet of collected core from 31 boreholes from 5 hydrocarbon and 2 chlorinated solvent sites. Data analyses include comparisons within a site, intra-site comparisons, and between sites, inter-site comparisons. Tools are developed in gINT™ to automate transformation of collected data into vibrant visual graphical outputs. First, for every borehole, a graphic is generated that includes a comprehensive panel of geology, contaminants of concern and fluid saturations properly presented by depth. Building on this, distributions of contaminants as a function of transmissive or low-k zones are resolved. Lastly, key attributes of mass distribution are compared across individual sites (intra-site comparisons) and between sites (inter-site comparisons). Our analysis presents a first-ever quantification of distribution of contaminant mass in transmissive and low-k zones. The analysis begins with processing concentration data-by-depth to produce the total mass of contaminants in each borehole, the mass of contaminants in transmissive zones, and the mass of contaminants in low-k zones. The contaminant mass in a borehole is presented for each contaminant individually and as sum of all contaminants. The visualization of this data is not intuitive due to the ranges of contaminant mass in place. Hydrocarbons contaminated sites have contaminant masses that range from less than half a kilogram to about 30 kilograms of contaminants per m2. Chlorinated solvent contaminated sites have contaminant masses that vary from less than 240 micrograms to right under 2.5 kilograms of contaminants per m2. The data is processed such that boreholes and sites with broad ranges of conditions can be compared. Data is presented as percent of contaminant mass in transmissive zones by borehole; the percent of contaminant mass in low-k zones by borehole, the percent of borehole that is transmissive, and percent of borehole that is low-k. Unlike previous data that required a y-axis formatted to a log scale, this data is visualized on a plot with the y-axis set at 0-100%. The fraction of a borehole that is low-k ranges between 0% and 94% with a median value of 52%. Secondly, the fraction of total contaminant mass stored in low-k zone ranges from 1% to 96% with a median value of 46%. Illustrations of the tendency for mass storage in low-k zones are presented through difference in percent of borehole that is low-k and percent of contaminants in a borehole in low-k zones. The calculations defined a positive difference as preference for transmissive zones and a negative difference as preference for low-k zones. Data presented characterized the 18 hydrocarbon contaminated boreholes, 12 chlorinated solvent contaminated boreholes, and all 30 contaminated boreholes respectively. Key insights include • Hydrocarbon contaminated boreholes showed statistically significant preference for low-k zones if the unit difference of percent of borehole that is low-k and percent of contaminants in a borehole in low-k zones was less than -24%. • Chlorinated solvent contaminated boreholes showed statistically significant preference for low-k zones if the unit difference of percent of borehole that is low-k and percent of contaminants in a borehole in low-k zones was less than -11%. • Remediated chlorinated solvent boreholes presented a preference for low-k zones where their non-remediated counterparts showed preference for transmissive zones. • All contaminated boreholes showed statistically significant preference for low-k zones if the unit difference of percent of borehole that is low-k and percent of contaminants in a borehole in low-k zones was less than -19%. • As an example, this thesis provides a unique documentation of benzene persisting in low-k zones. The presence or absence of benzene in low-k zones will have a large implication with respect to the longevity of benzene in monitoring wells and the efficacy of remedial measures that address the longevity of benzene in monitoring wells. Overall, cryogenic core collection and advanced analytics provides a practical means of quantifying contaminant occurrence in transmissive and low-k zones and an improved basis for anticipating the benefits of site remedies.
Keywords: cryogenic core collection; remediation; hydrocarbon chlorinated solvent; contaminant hydrology; large data